1986
DOI: 10.1577/1548-8659(1986)6<290:ooabti>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Anadromous Brown Trout in Two Lower Columbia River Tributaries

Abstract: In the Pacific northwest, brown trout (Salmo trutta) are found in selected streams and lakes east of the Cascade Mountain Range but have not been reported heretofore from coastal streams or tributaries of the lower Columbia River. Two brown trout were captured—one in 1979 at Kalama Falls salmon hatchery and the other in 1984 in Herrington Creek, a tributary of the South Fork Toutle River in Washington. Both fish probably came from previous plantings elsewhere. Viable anadromous populations via upriver or lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…and Pacific lamprey Lampetra tridentata. A single adult brown trout Salmo trutta was captured in Herrington Creek in October 1984 (Bisson et al 1986), but no juveniles of this species have been found there. We sampled fish populations twice after stocking in 1983 and 1984, and once after stocking in 1985 and 1986.…”
Section: Methodsmentioning
confidence: 99%
“…and Pacific lamprey Lampetra tridentata. A single adult brown trout Salmo trutta was captured in Herrington Creek in October 1984 (Bisson et al 1986), but no juveniles of this species have been found there. We sampled fish populations twice after stocking in 1983 and 1984, and once after stocking in 1985 and 1986.…”
Section: Methodsmentioning
confidence: 99%
“…Self-sustaining populations of brown trout outside their native range threaten native species via predation and competition (Idyll 1942;Bisson et al 1986; Sánchez-Hernández 2020) but also have considerable economic importance across the globe (Ahn et al 2000;O'Reilly et al 2006;O'Reilly 2015;Blicharska and Rönnbäck 2018). In contrast, spawning populations of coastal cutthroat trout have not been documented outside their native range, and efforts to transplant them have been limited (Crawford and Muir 2008) thus distribution patterns for coastal cutthroat have not changed significantly over the last 200 years (Metcalf et al 2012).…”
Section: Distributionmentioning
confidence: 99%
“…However, in other areas non-native populations of brown trout have been protected by management agencies and are highly prized for their economic value associated with fisheries, particularly for fluvial populations (Jones and Closs 2018). Interestingly, anadromous brown trout have been reported from watersheds also containing native coastal cutthroat (Idyll 1942;Bisson et al 1986). Given the overlap in ecological niche and trophic position of the two species, sympatric existence would likely be to the detriment of native cutthroat, as has been seen in landlocked sympatric populations in the Yellowstone Lake system (Al-Chokhachy and Sepulveda 2019).…”
Section: Managementmentioning
confidence: 99%